# Repeat Exercise 6 using the method of False Position. a. ex + 2−x + 2 cos x − 6 = 0 for 1 ≤ x ≤ 2 b. ln(x − 1) + cos(x − 1) = 0 for 1.3 ≤ x ≤ 2 c. 2x cos 2x − (x − 2)2 = 0 for 2 ≤ x ≤ 3 and

Repeat Exercise 6 using the method of False Position.

a. ex + 2−x + 2 cos x − 6 = 0 for 1 ≤ x ≤ 2

b. ln(x − 1) + cos(x − 1) = 0 for 1.3 ≤ x ≤ 2

c. 2x cos 2x − (x − 2)2 = 0 for 2 ≤ x ≤ 3 and 3 ≤ x ≤ 4

d. (x − 2)2 − ln x = 0 for 1 ≤ x ≤ 2 and e ≤ x ≤ 4

e. ex − 3x2 = 0 for 0 ≤ x ≤ 1 and 3 ≤ x ≤ 5

f. sin x − e−x = 0 for 0 ≤ x ≤ 1 3 ≤ x ≤ 4 and 6 ≤ x ≤ 7

a. ex + 2−x + 2 cos x − 6 = 0 for 1 ≤ x ≤ 2

b. ln(x − 1) + cos(x − 1) = 0 for 1.3 ≤ x ≤ 2

c. 2x cos 2x − (x − 2)2 = 0 for 2 ≤ x ≤ 3 and 3 ≤ x ≤ 4

d. (x − 2)2 − ln x = 0 for 1 ≤ x ≤ 2 and e ≤ x ≤ 4

e. ex − 3x2 = 0 for 0 ≤ x ≤ 1 and 3 ≤ x ≤ 5

f. sin x − e−x = 0 for 0 ≤ x ≤ 1 3 ≤ x ≤ 4 and 6 ≤ x ≤ 7

## This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

**Related Book For**